SILVIA BENEDITO: ATMOSPHERE ANATOMIES: ON DESIGN, WEATHER AND SENSATION - GARCIA-GERMAN TRUJEDA, JAVIER (Proyecto, Progreso, Arquitectura, 2022)
The book "Atmosphere Anatomies: On Design, Weather and Sensation" condenses the knowledge on design and atmosphere Silvia Benedito has developed over the last decade. In the light of climate change, Benedito champions the idea that spatial practices need to be reconceptualized as atmosphere or weather. In contrast to recent examinations of landscape architecture which have focused on other perspectives such as ecology or social sciences, Benedito claims the need to approach this design discipline as a meteorological phenomenon with physiological and psychological well-being implications.